2005
DOI: 10.3354/meps288021
|View full text |Cite
|
Sign up to set email alerts
|

Lack of allelopathic effects of the domoic acid-producing marine diatom Pseudo-nitzschia multiseries

Abstract: Many Pseudo-nitzschia species produce the toxin domoic acid, which accumulates in the food web during blooms, sometimes causing amnesic shellfish poisoning (ASP) in higher trophic levels, including humans. In addition, Pseudo-nitzschia species have been reported to form longlasting monospecific blooms, and a possible explanation for this could be allelopathic effects of the toxin, since domoic acid has been detected in high amounts in the surrounding medium in stationary growth phase. We therefore examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 54 publications
1
33
1
Order By: Relevance
“…Mixed culture experiments, however, showed no allelopathic effects of toxic P. multiseries on Chrysochromulina ericina, Heterocapsa triquetra, Eutreptiella gymnastica or Rhodomonas marina (Lundholm et al, 2005b). Similarly, additions of DA alone to the water had no allelopathic effects on 11 different phytoplankton organisms (Windust, 1992;Lundholm et al, 2005b). Thus, there is still no evidence that allelopathic effects are likely to contribute to the formation of long-lasting Pseudo-nitzschia blooms, or serve as an explanation for the evolution of DA production.…”
Section: Allelopathymentioning
confidence: 86%
See 1 more Smart Citation
“…Mixed culture experiments, however, showed no allelopathic effects of toxic P. multiseries on Chrysochromulina ericina, Heterocapsa triquetra, Eutreptiella gymnastica or Rhodomonas marina (Lundholm et al, 2005b). Similarly, additions of DA alone to the water had no allelopathic effects on 11 different phytoplankton organisms (Windust, 1992;Lundholm et al, 2005b). Thus, there is still no evidence that allelopathic effects are likely to contribute to the formation of long-lasting Pseudo-nitzschia blooms, or serve as an explanation for the evolution of DA production.…”
Section: Allelopathymentioning
confidence: 86%
“…It is therefore reasonable to speculate that this toxin could have an allelopathic effect. Mixed culture experiments, however, showed no allelopathic effects of toxic P. multiseries on Chrysochromulina ericina, Heterocapsa triquetra, Eutreptiella gymnastica or Rhodomonas marina (Lundholm et al, 2005b). Similarly, additions of DA alone to the water had no allelopathic effects on 11 different phytoplankton organisms (Windust, 1992;Lundholm et al, 2005b).…”
Section: Allelopathymentioning
confidence: 99%
“…In a highly mixed and disturbed environment, enhanced competitive ability for resources is probably the main factor favouring the dominance of certain species. However it is interesting to note that field and laboratory experiments have shown that Skeletonema and Pseudo-nitzschia species can release allelophatic compounds (e.g., Lundholm et al, 2005;Yamasaki et al, 2010;Xu et al, 2015) that could also be a factor in promoting mono-specific blooms in the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Lundholm et al, 2004), and trace metal limitation or toxicity (Maldonado et al, 2002). Evidence of allelopathic effects of DA, however, has not been found (Lundholm et al, 2005). DA is an amino acid and thus nitrogen is needed for its synthesis.…”
Section: Discussionmentioning
confidence: 99%